Kedudukan Living Law dalam Pembaharuan Hukum Pidana Indonesia - Dianto; Aida Dwi Putri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code marks a significant shift in Indonesia's criminal law reform by recognizing living law as a basis for criminal liability. This recognition reflects an effort to develop a national criminal law rooted in the social, cultural, and customary values that exist within society. However, the implementation of living law, particularly through Regional Regulations, raises concerns regarding the principle of legality, legal certainty, the distribution of authority between central and regional governments, and the protection of human rights. This study aims to examine the legal position of living law in Indonesia's criminal law reform, identify challenges in its implementation through Regional Regulations, and formulate a balanced legal framework for its future application. This normative legal research employs statutory, conceptual, and case approaches, with legal materials analyzed qualitatively through legal interpretation and argumentation. The findings reveal that living law strengthens legal pluralism and national legal identity but requires clear legal parameters to prevent arbitrary criminalization and discriminatory regional policies. The study proposes a harmonization model integrating living law, legality, constitutional principles, legal certainty, and human rights protection as its primary scientific contribution.